Geopolitik dan geostrategi Indonesia dalam menjaga kedaulatan di wilayah perbatasan - Fernida, Indri (Maliki Interdisciplinary Journal, 2026)
Indonesia, as an archipelagic country, holds a strategic geopolitical position while simultaneously facing various challenges in maintaining its territorial sovereignty, particularly in border areas. This study aims to analyze the role of Indonesia's geopolitics and geostrategy in maintaining its sovereignty in border areas and identify the challenges and strategic efforts undertaken. The method used is a qualitative approach with a literature review from various scientific journal sources. The results show that Indonesia's geopolitics, based on the Archipelago Insight, is the basis for maintaining territorial integrity, while geostrategy is realized through a multidimensional approach encompassing aspects of defense, development, and diplomacy. Furthermore, border areas face various challenges, both traditional such as territorial disputes and non-traditional such as transnational crime and development limitations. These conditions indicate that managing border areas requires not only a security approach but also sustainable economic and social development. Therefore, an integrated strategy is needed that involves strengthening defense, improving infrastructure, international cooperation, and empowering local communities. Thus, geopolitics and geostrategy play a crucial role in optimally and sustainably maintaining Indonesia's sovereignty in border areas.